The Influence of CEO Characteristics On Environmental, Social, & Governance (ESG) Strategies In Non-Financial Sector Companies Listed On The Indonesian Stock Ex-change (IDX) - Ika Safitri; Muhammad Saiful Hakim; Leonardus Arya Dewangga; Muhammad Haris Jauhari (Green Publisher Indonesia, 2024)
Global issues such as climate change, social injustice, and corporate misconduct have driven the emergence of the Environmental, Social, & Governance (ESG) concept as the foundation of business and investment strategies. While Indonesia has been a pioneer in ESG bond issuance, further steps are still needed to support national policies and ensure alignment with ASEAN and G20 goals in supporting sustainable finance. This study aims to determine the effect of CEO characteristics, namely Gender and Education, on the Environmental, Social, & Governance (ESG) of companies listed on the Indonesia Stock Exchange (IDX). The literature shows that Gender, Education, and CEO Experienxe affect the company's funding policy and capital structure, but the impact on ESG implementation is unclear. This study used a sample of 365 with a total of 73 companies. The data processing method used is panel linear regression analysis using RStudio software. The results showed that CEO gender has an insignificant positive effect, CEO education has a significant positive effect, and CEO experience has a significant negative effect on the ESG strategy score. The results of the study are expected to help companies in making policies to improve ESG and help investors in choosing ESG companies.